156k views
1 vote
9x-2y=-21 2x+3y=16 Substitution

1 Answer

6 votes

Answer:

x= -1 y= 6

Explanation:

Solve equation [2] for the variable y

[2] 3y = -2x + 16

[2] y = -2x/3 + 16/3

Plug this in for variable y in equation [1]

[1] 9x - 2•(-2x/3+16/3) = -21

[1] 31x/3 = -31/3

[1] 31x = -31

Solve equation [1] for the variable x

[1] 31x = - 31

[1] x = - 1

By now we know this much :

x = -1

y = -2x/3+16/3

Use the x value to solve for y

y = -(2/3)(-1)+16/3 = 6

Solution :

{x,y} = {-1,6}

User Bostonou
by
5.9k points